2019
DOI: 10.1108/jwl-05-2018-0073
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of learning content focus and collaborative learning on university teachers’ lifelong learning

Abstract: Purpose This paper aims to reveal the current status of China university teachers’ learning content focus (LCF) and collaborative learning (CL) and empirically examine the influential effects LCF and CL play on individual pursuit of lifelong learning (LLL) by investigating the mediating role of individual psychological empowerment (PE). Design/methodology/approach Descriptive analysis and structural equation modeling (SEM), including exploratory factor analysis (EFA), confirmatory factor analysis (CFA) and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…Finding also revealed that ELTs practice being life-long learners, which is consistent with studies highlighting the importance of life-long learning process in English language teaching (Dadvand & Behzadpoor, 2020) and higher/tertiary education teachers' consciousness of life-long learning required in professional development (Hursen, 2014;Zhou & Tu, 2019).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Finding also revealed that ELTs practice being life-long learners, which is consistent with studies highlighting the importance of life-long learning process in English language teaching (Dadvand & Behzadpoor, 2020) and higher/tertiary education teachers' consciousness of life-long learning required in professional development (Hursen, 2014;Zhou & Tu, 2019).…”
Section: Discussionsupporting
confidence: 86%
“…This parallels with Borg's (Borg, 2006b) language teacher characteristics which states "for language teachers, characteristics such as creativity, flexibility and enthusiasm are essential" (p. 24). This finding is also parallel to Zhou and Tu's (2019) study as teachers who accept that they are not 'All Knowing' wish to learn more to improve their skills and effectiveness. ELTs revealed that they believed and practised becoming a 21st century teacher.…”
Section: Discussionmentioning
confidence: 54%
“…When the literature was reviewed, studies were found on both adult education and lifelong learning. There are also studies which discuss and evaluate the views of academic staff in universities on adult education and lifelong learning (Ayçiçek & Yelken, 2016;Edokpolor & Omiunu, 2017;Konokman, Akay, & Demircioğlu, 2015;Mora, 2001;Walczak & Kálmán, 2018;Yildrim & Akcay, 2017;Zhou & Tu, 2019). The views of academic staff working in universities on lifelong learning and adult education were found in this study.…”
Section: Introductionmentioning
confidence: 54%
“…In view of upheavals in the business environment following the COVID-19 pandemic, organisations must respond swiftly to the "new normal" of conducting business by promoting employee lifelong learning to fill the knowledge and action gaps within the organisations. Zhou and Tu (2019) opined that many countries had unanimously agreed that lifelong learning was a significant approach in "constantly improving competent workforce…" (p. 442). Furthermore, lifelong learning was about making use of personal competences (Ozcan, 2011), and the complex interaction between humans and their surroundings (Jarvis, 2007).…”
Section: Lifelong Learningmentioning
confidence: 99%
“…The aforementioned constructs are important and relevant for an indepth study because existing literature have emphasised that quality of work life was crucial for the sustainability and effectiveness of an organisation (Bailey et al, 2017;Pruijt, 2000), led to job motivation (Yasini et al, 2011), as well as contributed to employee job performance, loyalty, and productivity (Kim et al, 2017;Nguyen et al, 2014). Additionally, employee engagement had a positive effect on employee task and job performance (Kim et al, 2012;Rana et al, 2014), while lifelong learning benefited both employees and organisations (Kyndt & Baert, 2013;Shan, 2018), as well as the overall workforce (Zhou & Tu, 2019). However, from a review of the literature, it was found that work arrangements discouraged lifelong learning in organisations (Hager, 2004), while at the same time, employee engagement at the workplace seemed to be declining, and disengagement appeared to be deepening (Bates, 2004;Richman, 2006).…”
Section: Introductionmentioning
confidence: 99%